Protein Nanotechnology Protocols, Instrumentation, and Applications - Vo-Dinh, Tuan.; Vo-Dinh, Tuan. (Methods in Molecular Biology,, 2005)
Rapidly emerging at the intersection of nanotechnology, materials science, and molecular biology, the field of nanobiotechnology promises to elucidate many life processes at the molecular-level previously invisible to human inquiry, and thereby dramatically to transform diagnostics, therapy, and drug discovery in this postgenomic world. In Protein Nanotechnology: Protocols, Instrumentation, and Applications, leading experts in nanobiotechnology comprehensively review the most recent advances in instrumentation and methodology, as well as their applications in genomics and proteomics. The authors provide a wide variety of techniques and methods for dealing with protein functions and structures at the nanoscale level, including nanostructured systems, nanomaterials, carbon nanotubes and nanowires, optical nanosensors, and nanoelectrodes. Among the highlights are techniques for the in vivo tracking of biochemical processes using fluorescent molecular probes and nanosensors, and the exploration of biochemical processes and submicroscopic structures of living cells at unprecedented resolutions using near-field optics. Also discussed is the development of nanocarrier methodology for the targeted delivery of drugs whose shells are conjugated with antibodies for targeting specific antigens. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and authoritative, Protein Nanotechnology: Protocols, Instrumentation, and Applications provides investigators a wide variety of readily reproducible techniques and methods for exploring both protein functions and structures at the nanoscale level and their powerful new biological and medical applications.